2014
DOI: 10.1509/jm.13.0509
|View full text |Cite
|
Sign up to set email alerts
|

Footprints in the Sands of Time: A Comparative Analysis of the Effectiveness of Customer Satisfaction and Customer–Company Identification over Time

Abstract: Previous research has identified customer satisfaction and customer-company identification as two of the most important concepts in relationship marketing. Yet despite their proclaimed importance, research on their long-term effectiveness is surprisingly scarce. Furthermore, comparative research acknowledging the concepts' different theoretical roots and illuminating the differences in their long-term effectiveness is lacking. In addition, little is known about how competitive actions affect the long-term effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 138 publications
5
115
1
2
Order By: Relevance
“…Together with previous research in the field of marketing, our findings may help practitioners find a better mix between these elements to ensure long-term success. For instance, Haumann et al (2014) recently studied the long-term effectiveness of customer satisfaction and customer-company identification on customer loyalty and willingness to pay, thereby demonstrating that the effects of identification were more persistent than the effects of customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with previous research in the field of marketing, our findings may help practitioners find a better mix between these elements to ensure long-term success. For instance, Haumann et al (2014) recently studied the long-term effectiveness of customer satisfaction and customer-company identification on customer loyalty and willingness to pay, thereby demonstrating that the effects of identification were more persistent than the effects of customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, brand loyalty refers to the behavioral perspective and has a more action-oriented focus. Therefore, both constructs have been established as separate latent variables and received a great deal of attention among marketing scholars (Haumann et al, 2014).…”
Section: Customer Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the sustained, long-term impact researchers attribute to consumer-brand identification (Haumann, Quaiser, Wieseke, & Rese, 2014), especially the effect of consumer-FBP identification seems to be of importance for sustained Third, an additional contribution of note is via the inclusion of perceived relationship investment as a direct and a moderating influence. This construct has typically been utilized in business-to-business contexts, but our research demonstrates its utility in the e-marketing context.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…The marketing concept suggests that when the buyers are satisfied would arouse their behavior and intention of repurchase, which concern that maintaining customer satisfaction is the most important long-term objectives of firms. According to Haumann (2014) in their study revealed that it usually costs more to serve new customers than repeat buyers, which means that repeat customers are more benefit to organizational cost structure. To be an organization, a primary strategic objective is to maximize customer intention rates to buy which emphasis on customer relationship management.…”
Section: Customer Loyaltymentioning
confidence: 99%